“Pain, Stress, and Emotions”: Uncontrolled trial of a single-session, telehealth, emotional awareness and expression therapy class for patients with chronic pain - Ziadni, Maisa S.; Sturgeon, John A.; Lumley, Mark A. (Frontiers in Pain Research, 2022)
Objectives Trauma- and emotion-focused chronic pain interventions, particularly Emotional Awareness and Expression Therapy (EAET), show much promise for reducing pain and improving functioning. We developed a novel, single-session, telehealth-delivered EAET class (“Pain, Stress, and Emotions”; PSE) and tested it on adults with chronic pain of mixed etiology. Methods After an initial developmental phase, we conducted an uncontrolled trial, providing PSE to 74 individuals with chronic pain (63.5% female; 64.9% White; 60.8% with pain duration >5 years) in four class administrations. Participants completed self-report measures (primary outcomes: pain intensity and pain interference) at baseline and multiple follow-ups to 12 weeks. Linear mixed-models examined changes over time, and effect sizes were calculated on change from baseline to 4-week (primary endpoint) and 12-week follow-ups. The trial was registered with clinicaltrials.gov (NCT05014126) Results Participants reported high satisfaction with the PSE class. Pain intensity showed a significant, medium reduction across time (p < .001; d = 0.60 at 4 weeks); one-quarter of participants had clinically meaningful pain reduction (≥30%). Pain interference had a large reduction (p < .001; d = 0.74). There were significant but smaller improvements in most secondary outcomes (ds = 0.15 to 0.55; ps < .01). Effects were generally maintained or increased at 12-week follow-up. Higher education and baseline ambivalence over emotional expression predicted greater pain reductions. Conclusions People taking this EAET class had reduced pain severity and interference and improvements in other pain-related outcomes. The single-session, telehealth class holds promise as an easily delivered, efficient, and potentially impactful intervention for some patients with chronic pain, although controlled trials are needed.